The Semantic Shadow: Structuring the Web for Adaptations - Bihler, Pascal; Cremers, Armin (Electronic Communications of the EASST, 2011)
This paper introduces the concept of the Semantic Shadow (SemS), a model for managing contentual and structural annotations on web page elements and their values. While the model is based on RDF, it supports a contextual weighting of the annotated information, allowing the annotator to specify the annotation values in relation to the evaluation context. This supports dynamic web page adaptation based on structural semantics on the page, whereas a context-awareness of the adaptation can be directly modeled alongside with the structural annotations.